ANALISIS PERCEPATAN WAKTU PELAKSANAAN PROYEK DENGAN PENAMBAHAN JAM KERJA (STUDI KASUS PEMBANGUNAN LAHAN PARKIR RUMAH SAKIT BANGLI MEDIKA CANTI) - I PUTU YANA HERMAWAN; I GEDE NGURAH SUNATHA; ANAK AGUNG RATU RITAKA WANGSA; KADEK ANDY SADEWA (Universitas Mahasaraswati K. Mataram, 2023)
Implementation of a construction project has a series of activities or jobs that are complex and interdependent on one another. Construction project development is carried out in several stages of work, one of which is making a work schedule. Work schedules are made to make it easier for each activity to be carried out sequentially and on time. In the implementation of the Parking Lot Construction Project at Bangli Medika Canti Hospital, there was a delay in weekly progress. To anticipate changes in implementation time, an acceleration of implementation time is carried out using the method of adding overtime hours. In this research, acceleration of implementation time was carried out using the method of adding overtime hours based on Microsoft Project. The data used in this study are in the form of a planned time schedule, realization time schedule, and weekly reports. The analysis was carried out to obtain the results of activities that can be accelerated and the project implementation time after being accelerated using the method of adding overtime hours. From the results of the analysis of the Microsoft Project, there are activities that can be accelerated, namely as many as 23 work items. After analyzing with the method of adding overtime hours on the implementation of the Parking Lot Development Project at Bangli Medika Canti Hospital, the project time was 122 days. This time is the same time at the initial planning. In the process of implementing the project, there was a delay in progress which resulted in a postponement of the project plan schedule to 129 days.